The Middle American species of Peridinetus Schönherr (Coleoptera: Curculionidae: Baridinae) - Prena, Jens (Zootaxa, 2010)
The weevil genus Peridinetus Schönherr is reviewed for mainland Middle America. Conophoria Casey is included in Peridinetus as a new junior synonym. Twenty-six species are recognized. Peridinetus ecuadoricus Casey stat. res., P. frontalis Chevrolat and P. pictus Kirsch are newly recorded for the study area. Newly described are P. illabes sp. n. (Panama), P. imperialis sp. n. (Costa Rica, Panama, Colombia, Ecuador), P. lugubris sp. n. (Costa Rica, Ecuador), P. notabilis sp. n. (Costa Rica), P. odone sp. n. (Costa Rica, Panama), P. pena sp. n. (Nicaragua, Costa Rica, Panama), P. rubens sp. n. (Costa Rica, Panama) and P. wyandoti sp. n. (Nicaragua, Costa Rica, Panama, Ecuador). The overlooked precedence of P. jelskii Chevrolat over P. maculiventris Chevrolat is reestablished. Conophoria cana dispersa Casey is a new junior synonym of P. canus Champion. Habitus images for most species and an identification key are provided.